Technology Of Wool Fiber Washing and Oil Removal (Texas Journal of Multidisciplinary Studies, 2021)
The composition of the washing solution consists of surfactant and soda. Under the influence of soda, the residual fat-wax substances in the fiber become soluble, and the surfactant emulsifies the fatwax substances that have passed into this soluble state, ensuring their release from the fiber